Acupuncture for Fibromyalgia: An Open-Label Pragmatic Study on Effects on Disease Severity, Neuropathic Pain Features, and Pain Catastrophizing. (25th February 2020) - Di Carlo, Marco; Beci, Giacomo; Salaffi, Fausto
Abstract : The treatment of fibromyalgia syndrome (FMS) is still far from being optimally coded, and pharmacological strategies are often unsatisfactory. Acupuncture plays a role among nonpharmacological intervention approaches; however, there is still no clarity as to when to integrate it into therapy. The objective of this study is to explore the role of acupuncture, in terms of efficacy on main disease severity measures and pain features, in patients with nonresponsive disease, defining nonresponsive FMS characterized by a revised Fibromyalgia Impact Questionnaire (FIQ-R) ≥39 and a Patient Health Questionnaire 15-item (PHQ15) ≥5 despite optimal drug therapy. Patients were treated with weekly sessions, for a total of eight acupuncture sessions. At the baseline and at the end of the treatment cycle, a comprehensive clinical evaluation was carried out to evaluate improvements in terms of disease severity and impact on neuropathic pain features (measured with the painDETECT questionnaire (PDQ)) and pain catastrophizing (measured with the Pain Catastrophizing Scale (PCS)). At the end of the eight-week treatment, patients experienced a significant improvement in all evaluated parameters (for FIQ-R, PDQ, and PHQ15 p < 0.0001, for PCS p = 0.001 ). Of particular note is the effectiveness on manifestations that are difficult to treat such as neuropathic pain features and on negative psychological perceptions such as pain catastrophizing. It can be stated that acupuncture can be proposed also in phases of high severity of disease. Intervention with multimodal strategies, including acupuncture, could be of great benefit to patients.